2016
DOI: 10.4028/www.scientific.net/amr.1140.239
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Hybrid Composites for Lightweight Structures: New Process Chain Approaches

Abstract: This publication describes new process chain approaches for the manufacturing of intrinsic hybrid composites for lightweight structures. The introduced process chains show a variety of different part and sample types, like insert technology for fastening of hollow hybrid shafts and profiles. Another field of research are hybrid laminates with different layers of carbon fiber reinforced plastics stacked with aluminum or steel sheets. The derived process chains base on automated fiber placement, resin transfer m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…A turbulent motion of the grits achieves a mild abrasion and removal of the substrate. With the help of an automated facility, the material's feed rate and the grit flow can be controlled to guarantee consistent process conditions [3]. The process proved to be reliable and provides comparably high shear strength values when comparing to chemical and conventional grit-blasting pre-treatments [15].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A turbulent motion of the grits achieves a mild abrasion and removal of the substrate. With the help of an automated facility, the material's feed rate and the grit flow can be controlled to guarantee consistent process conditions [3]. The process proved to be reliable and provides comparably high shear strength values when comparing to chemical and conventional grit-blasting pre-treatments [15].…”
Section: Methodsmentioning
confidence: 99%
“…Fiber metal laminates (FML) are hybrid composite materials consisting of metal sheets co-cure bonded to fiber reinforced plastic layers (FRP). No additional joining process is needed as adhesion is realized by the resin during its cure [1][2][3]. The resulting properties of the hybrid material need to be predictable when used in structural applications.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research activities have shown, that the gluing step can be integrated into the impregnation stage of the resin transfer moulding (RTM) process [13][14][15]. There, the metal component is placed inside the mould at the same time as the textile preform.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, one of the main focuses in the automotive industry should be on the development of new and efficient manufacturing and joining methods, and their integration into existing industrial processes. 9 For the production of such metal-FRP hybrid structures, intrinsic manufacturing techniques that integrate the joining process into the forming process of the FRP or the sheet metal, and thus enable a flat force transmission, are a convincing process technology. Common intrinsic manufacturing processes for hybrid structures are autoclave technologies, pressing technologies and resin injection processes, in which thermosetting and thermoplastic resins are used.…”
Section: Introductionmentioning
confidence: 99%